Dynamic tensile properties of cement mortar reinforced with face mask fibers: Performance evaluation and mechanism analysis - Zheng Wang; Tongge Cui; Bangbiao Wu; Wei Yao (Case Studies in Construction Materials)
The integration of face mask fibers (FMF) into cement materials has been proposed as a method to enhance material properties while mitigating pollution. Despite the validation of such advantages through extensive studies, the effects of mask fibers on the dynamic properties of the composite remain to be comprehensively investigated. This study examined dynamic tensile properties of cement mortar incorporating FMF at various volume percentages (0 %, 0.1 %, 0.2 %, 0.3 % and 0.5 %). X-ray Computed Tomography (CT) was utilized to assess specimen integrity. A split Hopkinson pressure bar (SHPB) system was employed to conduct dynamic Brazilian splitting tests, and quasi-static BD test was conducted for comparation. High-speed camera and digital image correlation (DIC) technology was used to analyse the specimen fracture during loading. Subsequently, both macro and micro-observations were made on the fragmented specimens. The results demonstrate that the inclusion of face mask generally reduces voids and microcracks within mortars, leading to material quality improvement for 8.6∼21.0 % characterized by CT value. As compared with the plain mortar, both the static and dynamic tensile strengths increase across all FMF mixtures, with the enhancement correlating with the material quality. The fracture energy density of the mortars showed significant improvement at higher loading rates (0.25–0.45 J/cm2 at 250 GPa/s), exhibiting pronounced rate sensitivity due to mask inclusion. The crushing pattern of the specimen also changes and shows certain microscopic characteristics. Based on these tensile properties, the optimum content of FMF is 0.3 %. These findings enhance the subsequent understanding of the effects of mask incorporation and provide a basis for determining the potential applications of such composite materials.